If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -3) + -2 = 5x + -43 Reorder the terms: 3(-3 + 3x) + -2 = 5x + -43 (-3 * 3 + 3x * 3) + -2 = 5x + -43 (-9 + 9x) + -2 = 5x + -43 Reorder the terms: -9 + -2 + 9x = 5x + -43 Combine like terms: -9 + -2 = -11 -11 + 9x = 5x + -43 Reorder the terms: -11 + 9x = -43 + 5x Solving -11 + 9x = -43 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -11 + 9x + -5x = -43 + 5x + -5x Combine like terms: 9x + -5x = 4x -11 + 4x = -43 + 5x + -5x Combine like terms: 5x + -5x = 0 -11 + 4x = -43 + 0 -11 + 4x = -43 Add '11' to each side of the equation. -11 + 11 + 4x = -43 + 11 Combine like terms: -11 + 11 = 0 0 + 4x = -43 + 11 4x = -43 + 11 Combine like terms: -43 + 11 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| 2x+1/8=5/3 | | 4(x+3)=2x+46 | | -1/4+1= | | 12+2x=42 | | -2.9c=8.7 | | -7=5(4x+3)-2 | | -8x-6=-6x-12 | | y=-0/4+1 | | 3(2x-5)=x-45 | | 4(4x-14)+x=5x-20 | | 5x+15=-3x-49 | | x/4-5=27 | | 3+4(n+2)=2n+3(n+4) | | x(x-15)=3(x-27) | | 0.67x+3.0=0.84x | | 23+2b=3(b+8)-3 | | 2(5x-4)=6x+12 | | -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 | | 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 |